USING TV COMMERCIALS AS AUTHENTIC MATERIALS FOR TEACHING LISTENING - Saputro, Fendik Wahyoe; Sulistyani, Sulistyani (English Education:Journal of English Teaching and Research, 2016)
The use of authentic materials is important in teaching EFL students due to its real life English language usage. For this reason, this article discusses the way how to use TV commercials as an authentic materials in teaching one of the skills in English, that is listening. This article serves several materials, activities, and steps of how we implement the usage of TV commercials as authentic materials to improve listening ablity of the students. These materials, activities and steps is aimed to encourage and to give the real life usage of English, so the students can implement it in their daily communication abroad. These strategies was collected through several articles reading and experts in EFL teaching. It is known that both EFL teachers and students have much to gain from TV commercials. TV commercials have visual, verbal and written images, interesting vocabulary and cultural features, and help students to improve their listening skills and to speak English in a more natural way. Keywords: TV commercials, authentic materials, teaching listening